Attitudinal aspects in the EEES-European Space Of Superior Education (Foro de Educacion, 2024)
The intent of this article is to bring the objectives of the European Space of Su- perior Education closer with one of the objectives of Viktor Frankl ́s speech logotherapy, i.e., how to define or reflect on the «sense of life» as a proposition to elaborate the plans of education from attitudinal values. In this understanding, the topic is fundamentally correlated between the perception of the world and of the person who possesses it; establishing this quality is critical to the most suitable understanding of the idea of education. On the basis of this, such reflections will be provided as designing improvement plans for the students, respecting the individual objectives, group objectives, and the legitimate concept of school as a favorable space to the development of skills. Therefore, the logical plan of this article is to effortlessly explain the respec- tive discussions of attitudinal values with the objectives of «Bologna» In this manner, the ped- agogical methods must take into account the opinions of the students in any decision of their education. Finally, this article defends the propositions of the EEES from the theoretical contri- butions of speech logotherapy.